The Role of Islamic Financial Technology in Strengthening MSME Resilience and Ethical Financing - Bambang Sugiharto; H. Harkim; Jenny Ester Pandiangan; Nickytha Linch De Hans Lumban Gaol (Golden Ratio of Auditing Research, 2026)
This study examines the role of Islamic financial technology (Islamic FinTech) in strengthening the resilience and ethical financing of micro, small, and medium enterprises (MSMEs). Employing a systematic literature review (SLR) of sixty-two academic and policy publications from 2015–2025, the research synthesizes key findings on how Sharia-based digital finance empowers MSMEs through inclusive, transparent, and sustainable mechanisms. The results show that Islamic FinTech enhances MSME resilience by facilitating access to Sharia-compliant financing, reducing transaction barriers, and promoting risk-sharing through mudharabah and musyarakah contracts. Furthermore, it integrates ethical values derived from maqāṣid al-sharīʿah, reinforcing justice, trust, and accountability in digital financial systems. The study also reveals that Islamic FinTech contributes to sustainable development by supporting gender inclusion, digital literacy, and environmentally responsible investment. Nevertheless, challenges remain in governance, financial literacy, and regulatory harmonization between Islamic law and technological innovation. The paper concludes that Islamic FinTech is not merely a digital intermediary but an ethical ecosystem that combines technology and faith to foster equitable, resilient, and sustainable economic growth. Future research should explore longitudinal case studies and cross-regional comparisons to assess the long-term social and financial impacts of Islamic FinTech in Muslim-majority economies.